Noise uncertainty effect on multi-channel cognitive radio networks - Amira Osama; Heba A. Tag El-Dien; Ahmad A. Aziz El-Banna; Adly S. Tag El-Dien (Institute of Advanced Engineering and Science, 2020)
Achieving high throughput is the most important goal of cognitive radio networks. The main process in cognitive radio is spectrum sensing that targets getting vacant channels. There are many sensing methods like matched filter, feature detection, interference temperature and energy detection which is employed in the proposed system; however, energy detection suffers from noise uncertainty. In this paper a study of throughput under noise fluctuation effect is introduced. The work in this paper proposes multi-channel system; the overall multi-channel throughput is studied under noise fluctuation effect. In addition, the proficiency of the network has been examined under different number of channels and sensing time with noise uncertainty.